Pengaruh Desain Kemasan Terhadap Pembelian Impulsif yang Dimediasi Emosi Positif - Widya Nur Fauziyah; Lia Siti Julaeha (Peneliti.net, 2022)
Entering the current era, which is growing rapidly, many cultures have entered, one of which is Korean culture. In this case, culture and anything that smells of Korea quickly becomes a trend. Super Junior is a boy band that has been named the